Pemberian Diet Diabetes Mellitus, Tinggi Protein dan Rendah Garam pada Pasien Diabetes Mellitus dengan Riwayat Stroke dan Kondisi Gangren Pedis Dekstra Disertai Tindakan Pembedahan Amputasi Bawah Lutut - Zahra Aillsa Zulkarnain; Farapti Farapti (Universitas Airlangga, 2024)
Background: Diabetes mellitus is a metabolic disease caused by increased blood glucose levels. One type of diabetes mellitus is type 2. Type 2 diabetes mellitus is caused by impaired insulin secretion, insulin resistance, other factors such as obesity, exercise, stress, and aging. One of the effects of diabetes mellitus is gangrene characterized by necrosis and infection of the inner soft tissue. Diabetics are susceptible to infections in foot which then develop into gangrene. Patients who have suffered from diabetes mellitus for years will tend to be at risk of developing ulcers which can result in amputation. Objectives: The purpose of writing this article is to knowing the nutrition care process to type 2 diabetes mellitus patient with a history of stroke, gangrene pedis dextra condition, and below knee amputation surgery Methods: The case study was conducted in November 2023 on inpatients of X Gresik Hospital. Data was obtained through 1x24-hour food recall observation before the patient entered the hospital and 3x24-hour food recall while in the hospital, interviews, direct observation, anthropometric measurements, medical record data, and literature studies. Intake data was processed using the Nutrisurvey application to determine the patient's daily intake. Results: After monitoring and evaluating for 3 days of intervention, the results showed that food intake had decreased on the 2nd day, classified as a severe deficit because after the amputation process and decreased appetite, while on the 3rd day, food intake had increased significantly, classified as a moderate deficit, characterized by reduced nausea and increased appetite. The biochemical data up to day 3 was classified as still abnormal, which was influenced by the amputation. Conclusions: The increase in food intake was seen significantly on the last day of intervention, when the results were quite significantly comparable to those of patients who had undergone amputation and had no complaints of nausea. Overall, the intervention provided was achieved.